Finding Meaning in Loss: The Role of Attachment Styles, Coping Strategies, and Resilience - Seyam, Salma (AUC Knowledge Fountain, 2025)
Grief is a deeply personal yet universal experience impacted by personal, social, and cultural factors. The present study examines how attachment styles, coping mechanisms, and resilience impact both grief intensity and the ability to find meaning after a loss, within an Egyptian sample. While previous studies have explored the experience of grief, few have looked at these factors within a Middle Eastern cultural context. A total of 140 bereaved Egyptians who experienced the loss of a loved one within the past three years completed standardized measures assessing grief intensity (Prolonged Grief Disorder-Revised; PG-13-R), coping strategies (Brief COPE), meaning-making (Grief and Meaning Reconstruction Inventory; GMRI), resilience (Brief Resilience Scale; BRS), and attachment styles (Experiences in Close Relationships Scale-Revised; ECR-R). Results indicated that insecure attachment styles (i.e., anxious and avoidant attachment styles) and avoidant coping were associated with less adaptive meaning-making following a loss, while emotion-focused coping and resilience fostered greater meaning-making. Avoidant attachment, avoidant coping, and problem-focused coping were associated with higher grief intensity, whereas resilience served as a protective factor. Anxious attachment showed no correlation with grief intensity. Mediation analyses identified avoidant coping as a full mediator and resilience as a partial mediator between grief intensity and meaning-making. Contextual factors such as experiencing multiple losses in the past three years, degree of closeness to the deceased, and lack of support further exacerbated the struggle in finding meaning. These insights highlight the nuanced interplay between internal and external factors in shaping the experience of grief. These findings emphasize the need for culturally attuned grief interventions that address attachment patterns, foster adaptive coping, and strengthen resilience to support the meaning-making process following a loss.